2017
DOI: 10.3892/ol.2017.5580
|View full text |Cite
|
Sign up to set email alerts
|

Role of endoplasmic reticulum stress on cisplatin resistance in ovarian carcinoma

Abstract: Abstract. Endoplasmic reticulum (ER) is an essential site of cellular homeostasis regulation. ER stress (ERS) may induce autophagy in tumor cells that escape from apoptosis. The present study examined the effects and mechanism of ERS on cisplatin (DDP) sensitivity in ovarian carcinoma. SKOV3 tumor cells treated with Saquinavir were subjected to western blot and reverse transcription-quantitative polymerase chain reaction analysis to determine protein and messenger RNA (mRNA) expression levels of mechanistic ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…This emphasize on the different outcomes of ER stress in different experimental systems. At the same time, dose‐dependent stimulation of ER stress and subsequent autophagy may significantly suppress apoptosis . Certainly, stimulation of autophagy by 2‐DG in cisplatin‐treated HCT116 cells attenuated the apoptotic response.…”
Section: Discussionmentioning
confidence: 95%
“…This emphasize on the different outcomes of ER stress in different experimental systems. At the same time, dose‐dependent stimulation of ER stress and subsequent autophagy may significantly suppress apoptosis . Certainly, stimulation of autophagy by 2‐DG in cisplatin‐treated HCT116 cells attenuated the apoptotic response.…”
Section: Discussionmentioning
confidence: 95%
“…Activating ERS has attracted a great deal of attention for cancer therapy due to the fact that ERS can effectively enhance tumor cell apoptosis [16]. ERS can decrease cisplatin sensitivity to ovarian carcinoma cells by regulating cell autophagy via the pathways of mTOR and Beclin1 [17]. Chen et al demonstrated that cxc195 and ERS induced apoptosis, inhibited phosphoinositide 3-kinase (PI3K)/AKT/mTOR signaling pathway in HepG2 cells [18].…”
Section: Introductionmentioning
confidence: 99%
“…Expression of ER stress markers such as GRP78 is increased in tissue specimens from endometrioid endometrial carcinomas at both mRNA and protein levels 20 . In addition, levels of GRP78 could affect the sensitivity to cisplatin by regulating autophagy and apoptosis in EOC [21][22][23] and may be involved in EOC resistance to platinum-based therapy 24 . Like GRP78, PDI also has a dual role in cell death and survival during ER stress.…”
mentioning
confidence: 99%